2006
DOI: 10.1111/j.1365-2966.2006.10050.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of eclipsing binary light curves – II. Statistical analysis of OGLE LMC eclipsing binaries

Abstract: In the first paper of this series, we presented EBAS – Eclipsing Binary Automated Solver, a new fully automated algorithm to analyse the light curves of eclipsing binaries, based on the ebop code. Here, we apply the new algorithm to the whole sample of 2580 binaries found in the Optical Gravitational Lensing Experiment (OGLE) Large Magellanic Cloud (LMC) photometric survey and derive the orbital elements for 1931 systems. To obtain the statistical properties of the short‐period binaries of the LMC, we construc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 32 publications
7
45
2
1
Order By: Relevance
“…Since these values will be obtained as the result of a well-defined, magnitude-limited photometric survey, they will provide large amounts of new data for statistical studies of spectroscopic binaries, including, e.g., the distribution of orbital period (Duquennoy & Mayor 1991;Mazeh et al 2006) and the relation between orbital period and eccentricity (Halbwachs et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Since these values will be obtained as the result of a well-defined, magnitude-limited photometric survey, they will provide large amounts of new data for statistical studies of spectroscopic binaries, including, e.g., the distribution of orbital period (Duquennoy & Mayor 1991;Mazeh et al 2006) and the relation between orbital period and eccentricity (Halbwachs et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect could result from a larger high-z population of small galaxies resembling low-z GRB host galaxies, seen as evolution in the galaxy luminosity function (e.g., Ryan et al 2007). An additional possibility is that, if the massive stellar binary fraction decreases with declining metallicity, as might be evidenced in the LMC (Mazeh et al 2006), the number of potential single-star progenitors may increase.…”
Section: Potential Sources Of Evolutionmentioning
confidence: 99%
“…Intriguingly, they observed that the distribution in log P is flat on the 2-10 days interval and that the detected frequency of their target stars is significantly smaller than the frequency deduced by dedicated RV surveys. The details on these findings are also given by Mazeh et al (2006b).…”
Section: First Bites On Large Databasesmentioning
confidence: 99%
“…Yet there are two important novelties of their approach: instead of inclination the authors introduced the impact parameter -the projected distance between the centers of the two stars during the primary eclipse, measured in terms of the sum of radii -and they introduced a new "alarm" statistics, the goal of which is to automatically discriminate best-fit χ 2 values from still apparently acceptable values, but corresponding to distinctively wrong solutions. A follow-up application of EBAS on 938 OGLE LMC binaries with B-type main-sequence primary stars (Mazeh et al 2006a) yielded the distributions of the fractional radii of the two components and their sum, the brightness ratios and the periods of the short-period binaries. Intriguingly, they observed that the distribution in log P is flat on the 2-10 days interval and that the detected frequency of their target stars is significantly smaller than the frequency deduced by dedicated RV surveys.…”
Section: First Bites On Large Databasesmentioning
confidence: 99%